Star polymers in good solvents from dilute to concentrated regimes: Crossover approach - Lue, L.; Kiselev, S.B. (Condensed Matter Physics, 2002)
An introduction is given to the crossover theory of the conformational and thermodynamic properties of star polymers in good solvents. The crossover theory is tested against Monte Carlo simulation data for the structure and thermodynamics of model star polymers. In good solvent conditions, star polymers approach a “universal” limit as N → ∞ ; however, there are two types of approach towards this limit. In the dilute regime, a critical degree of polymerization N∗ is found to play a similar role as the Ginzburg number in the crossover theory for critical phenomena in simple fluids. A rescaled penetration function is found to control the free energy of star polymer solutions in the dilute and semidilute regions. This equation of state captures the scaling behaviour of polymer solutions in the dilute/semidilute regimes and also performs well in the concentrated regimes, where the details of the monomer-monomer interactions become important. Подано вступ до кросоверної теорії конформаційних і термодинамічних властивостей зіркових полімерів у добрих розчинниках. Кросоверну теорію перевірено порівнянням з даними Монте Карло обчислень структурних і термодинамічних властивостей моделі зіркових полімерів. В умовах доброго розчинника властивості зіркових полімерів прямують до “універсальної” границі N → ∞ ; однак, є два різних способи прямування до цієї границі. В розведеному режимі, критичний ступінь полімеризації N∗ відіграє таку ж роль, як число Гінзбурга в теорії кросоверу в простих рідинах. Функція проникнення визначає вільну енергію розчинів зіркових полімерів в розведеній і напіврозведеній ділянках. Це рівняння стану описує основні риси скейлінгової поведінки полімерних розчинів в розведеному/напіврозведеному режимах і добре працює також в концентрованому режимі, де стають важливими деталі взаємодії між мономерами.